1997
DOI: 10.1094/pdis.1997.81.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Sphaeropsis sapinea Morphotypes Differ in Aggressiveness, but Both Infect Nonwounded Red or Jack Pines

Abstract: Two morphotypes of Sphaeropsis sapinea, designated A and B, are recognized in the north central United States. Nonwounded seedlings of red (Pinus resinosa) and jack pine (P. banksiana) were inoculated with conidial suspensions of isolates of each morphotype obtained from hosts in Michigan, Minnesota, and Wisconsin. Wounded seedlings were inoculated with water agar plugs colonized by these isolates. Both morphotypes penetrated both hosts without wounding. On nonwounded seedlings the frequency of symptoms was 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 12 publications
3
58
0
Order By: Relevance
“…The A morphotype seems to be dominant in all areas where disease has been reported. Pathogenic tests generally demonstrated a higher virulence for A and C than for B [21][22][23][24]214]. Several studies with vegetative compatibility groups and molecular markers showed a high genetic variability of S. sapinea morphotype A in some areas, e.g.…”
Section: Sphaeropsis Sapinea-pinusmentioning
confidence: 99%
“…The A morphotype seems to be dominant in all areas where disease has been reported. Pathogenic tests generally demonstrated a higher virulence for A and C than for B [21][22][23][24]214]. Several studies with vegetative compatibility groups and molecular markers showed a high genetic variability of S. sapinea morphotype A in some areas, e.g.…”
Section: Sphaeropsis Sapinea-pinusmentioning
confidence: 99%
“…However, endophytic isolates of the ' B ' morphotype have been routinely recovered from cones of Mexican pines and have more recently been isolated in P. radiata cones from California (unpubl.). The ' B ' morphotype isolates are also less aggressive pathogens than those of the ' A ' morphotype (Blodgett & Stanosz 1997. Thus, the ' B ' morphotype is not only associated with disease, but can also be an endophyte in asymptomatic tissue.…”
Section: Origin Of Sphaeropsis Sapinea In the Southern Hemispherementioning
confidence: 99%
“…In north central USA, D. pinea and D. scrobiculata coexist on Pinus banksiana (Palmer et al 1987, Palmer 1991, Blodgett & Stanosz 1997. P. radiata forms associations with D. pinea in exotic plantations but apparently only with D. scrobiculata in its native range.…”
Section: Discussionmentioning
confidence: 99%
“…This separation of cryptic species fits well with what is known of the biology of the two species. D. pinea is a virulent pathogen found throughout the world (Burgess & Wingfield 2002, Burgess, Wingfield & Wingfield 2004, whereas D. scrobiculata has a more limited range, principally the North-Central USA, and has low levels of pathogenicity (Palmer et al 1987, Blodgett & Stanosz 1997. Where their ranges overlap, the two morphotypes have been found to coexist on the same pine species and trees (Palmer et al 1987).…”
Section: Introductionmentioning
confidence: 99%